Post COVID-19 Era: Leveraging on agri-food sector for SL’s economic revival - Weerahewa, Jeevika; Roy, Devesh (Wijeya Newspapers Ltd., 2020)
The impact of the COVID-19 pandemic on the economy of Sri Lanka like anywhere else in the world will be complex to predict in terms of magnitude, but directions are predictable. Being a trade dependent island nation, Sri Lanka would likely suffer from the expected recession in addition to the disruptions in global and domestic supply chains. Notwithstanding these effects, our research shows that the overall impacts on agri-food supply chains in Sri Lanka may not be the slayer that one would expect it to be, barring the prolonged disruptions and adverse policy stances in other countries. Every crisis invariably nests an opportunity. As the rebuilding and revival of the economy eventuates, this article proposes three pivotal heads of interventions to make capital of the agri-food chains to shepherd the revival of the Sri Lankan economy post COVID-19 i.e. after the storm.